An impervious sand used as separation layer in collapsible loess embankment: A case study. (June 2022) - Zhang, Haihong; Fan, Shanzhi; Lang, Lei; Gu, Kang; Shi, Rui; Xue, Ke; Li, Desheng
Abstract: In this study, a novel impervious sand is modified from the desert sand. It has a good waterproofing and thermal-isolating capacity. Hence. it was used as the separation layer in the collapsible losses embankment to prolong the service life. It has the advantages of lightweight, good waterproofing effect, and cycled usage. The application of impervious sand in collapsible losses embankment could constrain water immigration effectively. Hence, local collapsible losses could be used in highway construction, which means the construction cost could be saved to a large extent. In this study, an artificial fill and impervious sand of different thicknesses were both used in collapsible losses embankment. In-suit monitoring on soil temperature, water content, settlement, and strains of different directions were conducted for more than one year. Hence, the waterproofing effect between the artificial fill and impervious sand could be compared. Furthermore, the collapsible losses embankment side slope stability was calculated through a finite element model. The long-term performance of embankment stability, which took the filling loess's water content into consideration, was also calculated and compared between the separation layer made of artificial fill or impervious sand. Highlights: A novel impervious sand was introduced as waterproofing layer in loess embankment. The in-suit hydro-thermal and mechanical data was collected for comparative analysis. The waterproofing effect of impervious sand was compared with other fill material. The embankment side slope stability was analyzed based on Finite Element Method. The long-term stability was also analyzed in regard to the soil water content change.